ملخص مركز ثقافي جنين - احمد ابو الرب (My University, 2024)
This research is considered a graduation project in architecture under the title “Jenin Cultural Center.” The project aims to establish a multi-purpose cultural center in the city of Jenin to meet the needs of the local community and promote culture and arts in the region. Culture is one of the basic elements that define the identity of societies and reflects their traditions, values and creativity. Cultural centers play a pivotal role in preserving cultural heritage, developing the arts, and promoting community understanding. The need for these centers is increasing in developing cities, such as Jenin, to support cultural, social and economic growth..